2023
DOI: 10.3390/prosthesis5010006
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effectiveness Testing of a Novel 3D-Printed Multi-Material Orthosis in Nurses with Plantar Foot Pain

Abstract: Plantar foot pain is one of the most common musculoskeletal conditions affecting the foot. It is regularly experienced by the population with occupations that require prolonged standing hours, especially in nurses. The etiology of plantar foot pain remains unclear, but it is likely to be multi-factorial, with many associated risk factors including increased hours of standing. Orthoses and insoles are often recommended to plantar foot pain patients, however with minimal scientific advancements and limited custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Additionally, it is capable of producing designs with varying material properties across the same part (Dong et al 2019). (Chhikara et al 2023) used 3D printing in producing customised moulds for multi-material insoles. (Kumar and Sarangi 2023) used additive manufacturing to produce and test various lattice cell structures in order to determine the most suitable for insole manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is capable of producing designs with varying material properties across the same part (Dong et al 2019). (Chhikara et al 2023) used 3D printing in producing customised moulds for multi-material insoles. (Kumar and Sarangi 2023) used additive manufacturing to produce and test various lattice cell structures in order to determine the most suitable for insole manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…1,16 According to a study conducted by Sambataro et al, elastics have an impact not only on the teeth but also on the TMJ position. [17][18][19][20][21][22][23][24][25] Moreover, a study conducted by Tanaka et al demonstrated that the elastic modulus of the TMJ disk exhibits an increase with age. 26 The mechanical loading that the TMJ structures experience depends significantly on the disk's stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,27,28 The production of a CMI that meets the biomechanical requirements for damping and support is demanding from material and mechanical points of view, knowledge, and skills. 1,[3][4][5]7,15,21,27,28 It follows from the above that a fundamental assumption for the successful designing CMIs is to understand the correlation of the foot to posture 29 and other aspects of the musculoskeletal system, 1,[3][4][5][6][7][8][9] to perceive relationships to associated diseases and cognition of the biomechanics, 1,4,5,12 weight-bearing activities 1,3,[5][6][7]9 of humans, and pathological forces 1,3,[5][6][7]13 which affect the foot. In general, the main principle in the design of CMI is the correction of deformities, 1,3,[7][8][9] reductions of painful symptoms, [3][4][5]…”
Section: Introductionmentioning
confidence: 99%
“…In general, the main principle in the design of CMI is the correction of deformities, 1,3,[7][8][9] reductions of painful symptoms, [3][4][5][6][7][8][9][10] and adequate load distribution. 1,3,6,8,12 Pain in the lower limbs and muscle fatigue are characteristic symptoms of flat feet. [1][2][3][4][5][6][7][8][9][10] These severe accompanying phenomena make ordinary life miserable and are why a person seeks professional help.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation